Covering cover pebbling number - Lourdusamy A.,; Punitha Tharani A., (Utilitas Mathematica, 2009)
In a graph G with a distribution of pebbles on its vertices, a pebbling move is the removal of two pebbles from one vertex and the addition of one pebble to an adjacent vertex. The covering cover pebbling number, denoted by σ(G), of a graph G, is the smallest number of pebbles, such that, however the pebbles are initially placed on the vertices of the graph, after a sequence of pebbling moves, the set of vertices with pebbles forms a covering of G. In this paper we determine the covering cover pebbling number for complete graphs, paths, wheel graphs, complete r-partite graphs and binary trees.